2020
DOI: 10.1002/hpja.322
|View full text |Cite
|
Sign up to set email alerts
|

Promoting cervical screening among women experiencing homelessness and socio‐economic disadvantage in Sydney

Abstract: Issue Addressed: Australia's national cervical screening program has reduced rates of cervical cancer morbidity and mortality. However, these benefits have not been experienced by all women. A Cervical Cancer Screening Project was implemented with lay health educators to address inequitable screening access by women experiencing socioeconomic disadvantage. Methods: Resources and a training program were developed and piloted with the specialist homelessness services workforce in Sydney, NSW. Data was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It also aligns with findings outside of the TIP research field, whereby the ways in which health systems are financed is frequently reported as a barrier across the healthcare setting [ 2 , 7 ]. This is particulary evident in regrds to providing accessible and appropriate prevention, treatment and recovery services for those who experience disadvantage, including complex trauma [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also aligns with findings outside of the TIP research field, whereby the ways in which health systems are financed is frequently reported as a barrier across the healthcare setting [ 2 , 7 ]. This is particulary evident in regrds to providing accessible and appropriate prevention, treatment and recovery services for those who experience disadvantage, including complex trauma [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clients with experience of complex trauma can fail to attend appointments, or when they do find it difficult to engage with clinicians and may require flexible or longer appointments, and additional case management or care coordination [ 18 , 28 , 35 ]. Front-line clinicians and managers therefore argue for increased flexibility in service delivery and greater attention to the needs of disadvantaged or minority populations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A new screening program for cervical cancer has recently been introduced in Australia and there has been a decline in the partication rates for cervical screening finding as a variety of personal, practitioner, test‐related and logistical barriers negatively impact cervical screening. Lovell et al, 33 suggested that although there has been benefits not all women have experienced this. Women experiencing homelessness and socio‐economic disadvantage in Sydney benefited from increasing workforce capacity in this sector so sustained mulitfacedted health promotion efforts are required to increase access for these women.…”
Section: Equity Equality and Valuesmentioning
confidence: 99%
“…20 It is also known that women from lower socio-economic backgrounds have lower screening participation and may not have access to a bulk-billing provider to avoid the visit fee gap associated with cervical screening. 21 Participation in cervical screening is highest in inner regional areas and lowest in very remote areas and there is a clear positive association between participation and living in a higher socioeconomic area. 22…”
Section: Introductionmentioning
confidence: 99%